Citrus Herbicide Boom Sprayer Calibration - Stephen H. Futch; Masoud Salyani (EDIS)
Herbicide application equipment calibration is an essential component of any weed control or weed management program. Proper calibration will assure even distribution of material over the treated surface, thereby maximizing application efficiency. Improperly adjusted equipment will result in uneven distribution of spray material, delivering questionable application rates which may result in poor weed control and/or possible tree damage due to potentially high rates. Incorrect application rates may result in increased weed control costs as a result of over application of herbicide material or the need to repeat application due to poor weed control. This document is HS-1012, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 2005.